GEOLOGY AND GEOCHEMISTRY FROM APIAI GRANITE REGION ROCKS, SOUTH OF SÃO PAULO STATE - Godoy, Antonio Misson (2021)
The Apiaí Granitic Stock rocks are located in the south of São Paulo state, inserted in Apiaí, Araçaíba and Mina do Espirito Santo topographic maps, 1:50000 scale, near Apiaí city and related to the Apiaí Terrane Neoproterozoic granitogenesis evolution. The lithotypes occur intrusive in the Açungui Supergroup meso-to neoproterozoic metavulcanicsedimentary sequence rocks, limited by normal and tectonic contacts with Água Clara Formation and Lajeado Group rocks, characterized in the area by the Serra da Boa Vista and Mármore Apiaí formations. It constitutes a body of approximately 65 km², in the form of a fissure intrusion, elongated and aligned in the general NE-SW direction, with a length of about 16 km, imposed by the interference of the Quarenta-Oitava Shear Zone and the Carumbé, Espirito Santo and Areia faults. These rocks have a compact structure, but are deformed when associated with brittle/ductile faults at the marginal and internal zones of the stock. Rocks with porphyritic texture dominate, marked by the presence of pinkish and rare white potassic feldspar phenocrysts. The body is constituted by an association of serial and hiatal porphyritic monzogranite, occurring in two forms, in relation to the size and quantities of phenocrysts, in addition to the localized presence of pink and gray inequigranular facies. It is a high potassium calcium-alkaline granite, monzogranitic series, metaluminous, I type, associated with a syn-to late-collisional magmatic arc environment and its placement is linked to transtensive structures, correlated to fault zones. The genesis of these rocks is correlated to the magmatism evolution of the Barra do Chapéu Granite, belonging to the granitogenesis of the Três Córregos Granitic Complex, in an extensional environment of Ribeira Orogenesis collisional event.